Re-examining the accreditation system for public administration education: Basis for future reforms - Tingco, Madlyn D. (Philippine Journal of Public Administration; Vol 65 No 1&2 (2021), 2021)
The article explores comparisons of international and local accreditation systems for Public Administration (PA) education to identify prospects for harmonization. It looks into the accreditation processes and standards of the Accrediting Agency of Chartered Colleges and Universities in the Philippines, Inc. (AACCUP) as a local model vis-à-vis three international PA accrediting models: International Commission on the Accreditation of Public Administration Education and Training Programs (ICAPA), Network of Schools of Public Administration and Policy, Affairs and Administration (NASPAA), and European Association for Public Administration (EAPAA). The findings show that certain accreditation processes and standards of excellence may be integrated by the AACCUP as a way of responding to the internationalization of accreditation systems for the improvement of the quality of Public Administration education. Keywords: accreditation process; quality standards; Public Administration education; quality assurance; accreditation models